Abstinence from Cocaine and Sucrose Self-Administration Reveals Altered Mesocorticolimbic Circuit Connectivity by Resting State MRI - Lu, Hanbing (Mary Ann Liebert, Inc., 2014)
Previous preclinical studies have emphasized that drugs of abuse, through actions within and between mesocorticolimbic (MCL) regions, usurp learning and memory processes normally involved in the pursuit of natural rewards. To distinguish MCL circuit pathobiological neuroadaptations that accompany addiction from general learning processes associated with natural reward, we trained two groups of rats to self-administer either cocaine (IV) or sucrose (orally) followed by an identically enforced 30 day abstinence period. These procedures are known to induce behavioral changes and neuroadaptations. A third group of sedentary animals served as a negative control group for general handling effects. We examined low-frequency spontaneous fluctuations in the functional magnetic resonance imaging (fMRI) signal, known as resting-state functional connectivity (rsFC), as a measure of intrinsic neurobiological interactions between brain regions. Decreased rsFC was seen in the cocaine-SA compared with both sucrose-SA and housing control groups between prelimbic (PrL) cortex and entopeduncular nucleus and between nucleus accumbens core (AcbC) and dorsomedial prefrontal cortex (dmPFC). Moreover, individual differences in cocaine SA escalation predicted connectivity strength only in the Acb-dmPFC circuit. These data provide evidence of fronto-striatal plasticity across the addiction trajectory, which are consistent with Acb-PFC hypoactivity seen in abstinent human drug addicts, indicating potential circuit level biomarkers that may inform therapeutic interventions. They further suggest that available data from cross-sectional human studies may reflect the consequence of rather a predispositional predecessor to their dependence.